Tratamento da humidade ascensional no património histórico - De Freitas, V. P.; Guimarães, A. S. (Revista ALCONPAT, 2014)
Rising damp linked with the salts is a factor in old buildings walls degradation, which requires knowledge of its higrothermal behavior, as well as the treatment techniques and its effectiveness knowledge. The rising damp treatment is very complex and many of the techniques to solve the problem do not show the desirable effectiveness. The Building Physics Laboratory of the Faculty of Engineering of the University of Porto has developed numerical and experimental research that allowed the validation of a technology based on the wall base hygroregulated ventilation to treat rising damp, patent the system-HUMIVENT. This paper aims to describe the pathologies associated to rising damp; the advantages and disadvantages of the most common available technologies for its treatment; characterize the rising damp treatment system-HUMIVENT, their implementation in Portuguese buildings and the analysis of the obtained results. Keywords: rising damp, historical building, hygroregulated system